The use of authentic video in Russian as foreign language teaching on A1 level - Natalija A. Gridneva; Svetlana M. Vladimirova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The usage of authentic materials in foreign languages teaching is one of the basic requirements of communicative approach, which means the highest possible likening of educative process to that of a real communication. This article deals with possibilities of authentic videos usage at the initial stage of Russian as a foreign language training. The authors prove the necessity and relevancy of authentic videos usage already with the beginners and show the possible efficiency of such work, also, for sociocultural competence developing. Some possibilities of authentic videos usage at the initial training stage are exemplified by short films from popular Russian sketch comedies (particularly “Yeralash” and “Fitil”), which, as the authors show, have a variety of advantages over other kinds of materials. The authors offer some effective training practices (based on «Common European Framework of Reference: Learning, Teaching, Assessment» and «Russian Public Standard for Russian as a Foreign Language (Elementary Level - A1), which can be used for drilling and perfecting some basic phrases, especially needed in the everyday life.